Adherence to subcutaneous interferon beta-1a treatment among patients with relapsing multiple sclerosis: the MAIN-MS study - Al-Roughani, Raed; Zakaria, Magd; Cupler, Edward J.; Taha, Karim (Frontiers in Neurology, 2023)
Introduction and background Adherence is a critical factor for optimal clinical outcomes in multiple sclerosis (MS) treatment. This study investigated the adherence and clinical outcomes of MS patients treated with subcutaneous (sc) interferon (IFN) (β)-1a, an established immunomodulatory treatment for relapsing MS. The benefits of a patient support programme (PSP) were also studied. Methods This phase-IV prospective, observational multicentre study enrolled patients with relapsing MS who were treated with sc IFN β-1a for 24 months was conducted at 53 centres across 17 countries. The primary endpoint was adherence to sc IFN β-1a treatment, as assessed using Morisky Green Levine Medication Adherence Scale (MGLS) scores at 24 months. The MGLS is a self-reported diagnostic tool to address medication non-adherence, with a score ranging from 0 to 4, with 0 representing high adherence, 1–2 representing medium adherence, and 3–4 representing low adherence. Other endpoints included time to study and treatment discontinuation over 24 months, the proportion of relapse-free patients, and Expanded Disability Status Scale (EDSS) progression (defined as ≥1.0 point increase sustained for 3 months) at 24 months. A subgroup analysis was performed for endpoints based on patients assigned to PSP (yes/no—PSP versus non-PSP subgroup). Results Of the 577 patients enrolled, 408 had evaluable MGLS scores at 24 months. A total of 336 (58.2%; 95% confidence interval [CI]: 54.1–62.3%) patients reported high adherence, 57 (9.9%; 95% CIs: 7.6–12.7%) reported medium adherence, and 15 (2.6%; 95% CI: 1.5–4.3%) reported low adherence at 24 months. The PSP subgroup reported higher adherence (n = 206; 65.8%) than the non-PSP subgroup (n = 130; 56.5%). By 24 months, 52.2% of the patients were relapse-free and 17.2% patients experienced ≥1 relapse. Expanded Disability Status Scale progression was observed in 12.3% of patients. Over the 24-month period, 30.8% of the patients discontinued treatment, and the most common reasons for treatment discontinuation were adverse events (AEs, 10.4%), being lost to followup (7.1%), and a lack of efficacy (5.5%). Overall, 39.6% patients experienced ≥1 AE, which ranged from mild to moderate. Conclusion The study demonstrated high adherence to sc IFN β-1a treatment with an added benefit of PSP participation. More than half of the patients remained relapse-free over a 24-month period. No new safety concerns to sc IFN β-1a treatment were observed. Clinical trial registration https://clinicaltrials.gov/study/NCT02921035, NCT02921035.